Analysis of Transient Response and Harmonic Disturbances on the Tanker's Electrical System Based on Simulation - Sardono Sarwito; Eddy Setyo Koenhardono; Kirana Putri Taradipa Martha (International Journal of Marine Engineering Innovation and Research, 2018)
Basically a ship has a variety of conditions, namely cargo handling, anchoring, maneuvering, and sailing its requires large electricity consumption. The quality of the voltage is not good will cause damage to electrical equipment on board. Disturbances that occur in electrical system of MT. X may result in a decrease in the performance of existing electrical equipment on the vessel and affect a certain condition as in loading-unloading conditions the time required for loading and unloading becomes longer due to interference with the electrical system. The MT.X tanker system has 5 (five) main busbars: BUS 1, FEEDER PANEL, DSB 2, DSB 3 & 4, and DSB 6. The MT tanker. X has a generator of 3 units with a power of 680 kw each, a frequency of 60 hz and a voltage of 450 V. Transient disturbance analysis under loading-unloading condition occurs transient response due to starting ballast pump where the voltage rises and then drops within 0.5 seconds with the highest value of 100.44% at 4.01 seconds and the lowest value is 99.50% to 4.81 can then reach steady state conditions at 99.9%, which does not exceed the IEEE standard limits. In harmonic disturbances under loading-unloading conditions, in the feeder panel connecting the harmonic source with load at the 5th order, the value of VIHD is 8.77%, which exceeds the IEEE standard of 5%. While the value of VTHD in loading and unloading conditions also exceeded the predefined standard limits. After installation of the filter, it can be seen that the value of VIHD at the 5th order in loading-unloading condition decreased to 3.6% after the installation of filter on feeder panel, or equal to decrease as much as 5.17%. The decline in the value of VIHD has fulfilled the IEEE 519-2014 standard of 5% on each individual order. Meanwhile, VTHD value in loading-unloading condition also decreased, from 11.18% to 7.02%.